Effect of Austenite Transformation on Abrasive Wear and Corrosion Resistance of Spheroidal Ni-Mn-Cu Cast Iron - Medyński D.; Janus A. (Archives of Foundry Engineering, 2016)
Within the presented work, the effect of austenite transformation on abrasive wear as well as on rate and nature of corrosive destruction of spheroidal Ni-Mn-Cu cast iron was determined. Cast iron contained: 3.1÷3.4 %C, 2.1÷2.3 %Si, 2.3÷3.3 %Mn, 2.3÷2.5 %Cu and 4.8÷9.3 %Ni. At a higher degree of austenite transformation in the alloys with nickel equivalent below 16.0%, abrasive wear resistance was significantly higher. Examinations of the corrosion resistance were carried out with the use of gravimetric and potentiodynamic method. It was shown that higher degree of austenite transformation results in significantly higher abrasive wear resistance and slightly higher corrosion rate, as determined by the gravimetric method. However, results of potentiodynamic examinations showed creation of a smaller number of deep pinholes, which is a favourable phenomenon from the viewpoint of corrosion resistance.